A Study for Supply Chain Management Improvement - Olfa Jellouli (International Journal of Supply Chain Management, 2013)
The management of multi-site enterprises is very complex. However, it is true that it allows an advantage compared to companies mono-site and this article proves it. In the face of competition from more and more fierce thanks to the globalization of trade, businesses are confronted today with the challenge of an faster responsiveness through an effective information system. It is in this framework that I have developed this article.